Assessment Method for Course Outcome and Program Outcome In Outcome Based Education (OBE) - Zamri, Mohamed; Mohd Yusof, Taib; Mohamed Reza Zalani, Mohamed Suffian (2010)

(untitled)
Abstract—Outcome Based Education (OBE) has become the standard of practice in Higher Education Institutions especially those that offer programs in engineering. This paper introduces a method to measure students’ performance in respect to OBE concept. The flow of measurement is taken from students’ progress marks and also final exam. The marks are then converted whether they meet the course outcome set by instructor. After getting the course outcome score, contribution of each course to program outcome can be measured progressively until students complete their 4 year program. In getting the score Program Outcome, the instructor would plan earlier on the assessment question specification to program outcome. The method is found to be very practical to be implemented for any instructor to measure the course outcome and program outcome. In addition, it would contribute to the continuous quality improvement process as specified by Washington Accord as well as Engineering Accreditation Council, Malaysia.